2007
DOI: 10.1007/s10038-007-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and haplotypes of the gene encoding the estrogen-metabolizing CYP19 gene in Korean women: no association with advanced-stage endometriosis

Abstract: A variety of factors affect the development of endometriosis, including hormonal status and genetic factors. The growth of endometriosis is stimulated by local estrogen production in conjunction with circulating estrogen. The CYP19 gene encodes a steroid aromatase that catalyses the conversion of C-19 androgens to estrogens. This study investigated whether polymorphisms of the CYP19 gene are associated with the risk of advanced endometriosis in Korean women. Blood samples were collected from 224 female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Kim et al 16 reported that the frequency of the low type, which means that the TTTA copy number was under 10, was 55.5% and that of the high type (TTTA copy number with over 10) was 44.5% in 102 Korean control subjects. The similar report in a Korean population 17 is described in Table 3. Although (TTTA) 8 was not detected, this allele was the third most frequent allele in Caucasian and African-American populations, occurring at B12.5 and 2.5%, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Kim et al 16 reported that the frequency of the low type, which means that the TTTA copy number was under 10, was 55.5% and that of the high type (TTTA copy number with over 10) was 44.5% in 102 Korean control subjects. The similar report in a Korean population 17 is described in Table 3. Although (TTTA) 8 was not detected, this allele was the third most frequent allele in Caucasian and African-American populations, occurring at B12.5 and 2.5%, respectively.…”
Section: Resultssupporting
confidence: 68%
“…They observed could be explained by chance due to the number of analyses conducted and comparisons made; there are data to suggest that the chromosomal region 15q21.1, where CYP19A1 is located, may influence breast cancer progression [12]; likewise, the other studies by Kristensen et al showed that the examined CYP19 polymorphisms (rs700518: A>G,rs2236722: T>C, [TTTA]n repeat, and rs10046: T>C) were not significantly correlated with the hazard of infertility and endometriosis or endometriosis with ovarian chocolate cysts in Chinese women [16]. Many prior studies from Korean people [17], Japanese people [18], and Caucasian people [19], all of that showed no significant correlation of CYP19 gene polymorphisms with the hazard of chocolate cysts or endometriosis. The study by Hirose et al, [20] showed that in estrogen biosynthesis, the genetic polymorphisms (CYP19A1) are as well expected to affect the degradation or synthesis of estrogen, and then, lead to increase the breast cancer risk at codon 39 [21,22], the (rs2236722) polymorphism is created by the substitution of amino acids (Trp) with (Arg), while another study showed the Japanese women with the presence of these different alleles (Arg) lead to significantly decreased the developing of the breast cancer risk [23].…”
Section: Discussionmentioning
confidence: 96%
“…CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014. We have shown that there is a significant correlation between CYP19A1 rs2899470 and risk of endometriosis in a Chinese population.…”
Section: Discussionmentioning
confidence: 58%